Identification and Management of Abdominal Compartment Syndrome in the Pediatric Intensive Care Unit - Díaz, Francisco J.; Fernández, Alicia; Gotay, Felicita (Puerto Rico Health Sciences Journal, 2006)
Objective. Asses if Abdominal Compartment Syndrome (ACS) increases the morbidity and mortality of the Pediatric Intensive Care Unit patients and if early recognition and intervention with decompressive therapy will alter outcome and decrease mortality. Setting. Pediatric Intensive Care Unit of the University Pediatric Hospital –UPR Patients. All patients admitted to the PICU from July 1, 1999 to June 30, 2002 were enrolled in the study. Those having a distended and/or tense abdomen on physical examination were identified at risk for intraabdominal hypertension (IAH). IAH was diagnosed if the intra-abdominal pressure (IAP) was above 10 mmHg and with ACS if the IAH was accompanied by: hemodynamic instability, oliguria or anuria, metabolic acidosis and respiratory deterioration. Measurements and Main Results. 1052 patients were admitted to PICU. Ten patients with evidence of ACS were identified with an incidence of 0.9%. Ages ranged from 6 weeks to 12.3 years. Peak intravesical pressure measurements ranged from 17 to 39 mmHg. Inspiratory pressure was raised from a mean of 21.2 to 32.0 cmH2O. The PCO2 increased from a mean of 35.1 to 63 torr and the pH decreased from a mean of 7.40 to 7.12. Overall mortality was 40% for this patient population. Conclusions. The outcome of pediatric critical care patients depends on multiple variables. Now there is evidence that in a select group of patients IAH and ACS play a significant role in their morbidity and mortality. This makes it mandatory for clinicians taking care of this population to be increasingly aware of this condition.